2016
DOI: 10.11607/ofph.1512
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Herpes Simplex Virus Vector Encoding the Human Preproenkephalin Gene for Treatment of Facial Pain in Mice

Abstract: Aims To determine whether herpes simplex virus–based vectors can efficiently transduce mouse trigeminal ganglion (TG) neurons and attenuate preexisting nerve injury–induced whisker pad mechanical hypersensitivity in a trigeminal inflammatory compression (TIC) neuropathic pain model. Methods Tissue transduction efficiencies of replication-conditional and replication-defective vectors to mouse whisker pads after topical administration and subcutaneous injection were assessed using quantitative real-time PCR (q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…Surprisingly, in this study, infection with hsvPPE did not reverse thermal hyperalgesia and had no effect on morphine analgesia in nerve injured mice. This is different from previous studies showing a reduction of neuropathic pain in rodent models of nerve injury 18,49 , and capsaicin induced pain 15 . It is noteworthy that our behavioral studies were conducted at least two weeks post intradermal injection of the virus and nerve injury, and experiments included female mice.…”
Section: Discussioncontrasting
confidence: 99%
“…Surprisingly, in this study, infection with hsvPPE did not reverse thermal hyperalgesia and had no effect on morphine analgesia in nerve injured mice. This is different from previous studies showing a reduction of neuropathic pain in rodent models of nerve injury 18,49 , and capsaicin induced pain 15 . It is noteworthy that our behavioral studies were conducted at least two weeks post intradermal injection of the virus and nerve injury, and experiments included female mice.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, numerous DE miRNAs were detected and miR-122 was the most notably upregulated miRNA. It was previously reported that miR-122 is involved in the regulation of neuropathic pain (30); however, whether miR-122 regulates DNP remains elusive and further studies are required to determine this. Although DE miRNAs in the spinal cord of mice with DNP were screened and the differential expression of certain miRNAs was confirmed in the present study, the underlying mechanisms of miRNAs in DNP are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…RNA was reverse transcribed and quantified by quantitative real-time PCR. 21 Sprr1a, Gal, Atf3, and GAPDH TaqMan gene expression assays were purchased from Life Technologies Corporation (Carlsbad, CA). Real-time PCR was performed on an ABI Prism 7700 Sequence Detection system (PE Applied Biosystems, Foster City, CA, USA) in a 20 µl reaction volume consisting of final concentrations of 1X TaqMan Universal PCR master mix (PE Applied Biosystems) and 1× respective gene expression assays using default conditions.…”
Section: Methodsmentioning
confidence: 99%